Clinical outcomes and safety profile of Tenecteplase in wake‐up stroke. (23rd June 2020) - Ahmed, Hassan Khan; Logallo, Nicola; Thomassen, Lars; Novotny, Vojtech; Mathisen, Sara M.; Kurz, Martin W.
Abstract: Background: Tenecteplase has probably pharmacological and clinical advantages in the treatment of acute ischemic stroke. There are lacking data about safety and efficacy of tenecteplase in wake‐up stroke (WUPS). Aims: To investigate safety and efficacy of tenecteplase compared to alteplase in WUPS patients included in NOR‐TEST. Methods: WUPS patients in NOR‐TEST were included in the study based on DWI‐FLAIR mismatch. Included patients randomly assigned (1:1) to receive intravenous tenecteplase 0.4 mg/kg (to a maximum of 40 mg) or alteplase 0.9 mg/kg (to a maximum of 90 mg). Neurological improvement was defined as 1) favorable functional outcome at 90 days modified Rankin Scale (mRS) of 0 or 1 and 2) neurological improvement measured with the National Institutes of Health Stroke Scale (NIHSS) of 4 points within 24 hours as compared to admission NIHSS or NIHSS 0 at 24 hours. Results: Of 1100 patients from 13 stroke centers included in NOR‐TEST, 45 were WUPS patients. Of these, 5 patients were stroke mimics and excluded. Of the remaining 40 patients (3.6%), 24 were treated with alteplase (60%). There was no difference in the number of patients achieving a good clinical outcome (mRS 0‐1) in either treatment group. Patients treated with tenecteplase showed a better early neurological improvement (87.5% vs 54.2%, P = 0.027). No ICH was detected on MRI/CT 24‐28 hours after thrombolysis. Conclusions: In WUPS patients treated in NOR‐TEST, there was no difference in clinical outcomes at 90 days and no ICH events or deaths were observed in either alteplase‐ or tenecteplase‐treated patients. Clinical Trial Registration—URL: https://www.clinicaltrials.gov . Unique identifier: NCT01949948.